Pengaruh Penerapan Smart Card terhadap Lingkungan Masyarakat - Amanda, Silvia; Firdaus, Rayyan (Innovative: Journal Of Social Science Research, 2024)
One of the ideas of a Smart City is the Smart Card program. Law no. 23 of 2014 which regulates regional government, chapter XXI, entitled “Regional Innovation Articles 386-390,” regulates this initiative, which is a regional innovation. According to this law, regional governments must come up with new ideas to advance regional development. This research aims to determine the impact of using Smart Cards on the surrounding environment. This research uses a descriptive qualitative methodology that includes a literature review. The implementation of Smart Cards has an impact on the community environment, according to research findings, one of which is that the cards are used to assist with government administrative matters. The relationship between society and government in improving public services is in second place. When a card is linked to a preset app that tracks students' check-in and check-out times, the card can be used, for example, to track their attendance at school and send it to parents.